Temporal profile of body temperature in acute ischemic stroke: relation to infarct size and outcome. Issue 1 (December 2016) - Geurts, Marjolein; Scheijmans, Féline; van Seeters, Tom; Biessels, Geert; Kappelle, L.; Velthuis, Birgitta; van der Worp, H.
Abstract Background High body temperatures after ischemic stroke have been associated with larger infarct size, but the temporal profile of this relation is unknown. We assess the relation between temporal profile of body temperature and infarct size and functional outcome in patients with acute ischemic stroke. Methods In 419 patients with acute ischemic stroke we assessed the relation between body temperature on admission and during the first 3 days with both infarct size and functional outcome. Infarct size was measured in milliliters on CT or MRI after 3 days. Poor functional outcome was defined as a modified Rankin Scale score ≥3 at 3 months. Results Body temperature on admission was not associated with infarct size or poor outcome in adjusted analyses. By contrast, each additional 1.0 °C in body temperature on day 1 was associated with 0.31 ml larger infarct size (95% confidence interval (CI) 0.04–0.59), on day 2 with 1.13 ml larger infarct size(95% CI, 0.83–1.43), and on day 3 with 0.80 ml larger infarct size (95% CI, 0.48–1.12), in adjusted linear regression analyses. Higher peak body temperatures on days two and three were also associated with poor outcome (adjusted relative risks per additional 1.0 °C in body temperature, 1.52 (95% CI, 1.17–1.99) and 1.47 (95% CI, 1.22–1.77), respectively). Conclusions Higher peak body temperatures during the first days after ischemic stroke, rather than on admission, are associated with larger infarct size and poor functional outcome. This suggests that prevention of high temperatures may improve outcome if continued for at least 3 days.